Dawn and the surfer ghost - Martin, Ann M., 1955- (New York : Scholastic, 1993)
When a local surfer mysteriously disappears, Dawn fears his ghost is haunting the beach.
5.1
3-6
Keywords: Ghosts -- Fiction; Mystery and detective stories; Surfing -- Fiction; Ghost stories; Mystery fiction; Surfing -- Fiction